ONLINE LEARNING PERCEPTION DURING COVID-19 PANDEMIC VIEWED FROM HIGH SCHOOL STUDENTS - Junaedi Setiyono; Semi Sukarni; Abdul Ngafif (English Review: Journal of English Education, 2021)
The purpose of this study was to investigate SMA and SMK students' perceptions of online learning. Secondly, to examine whether the two schools differ greatly and to describe their perception of online learning based on their perceptions. There were 133 participants, comprising 61 SMA students and 72 SMK students. The data was collected using Likert scale questionnaires and an interview. To analyze the data, the authors carried out descriptive and inferential analyzes of the quantitative data, while a qualitative thematic analysis was used. The finding of the study shows that there was a significant difference in the perception of online learning between SMA and SMK students. The high perception was obtained from SMA students, while medium perception was showed by SMK students. Based on the thematic analysis, it showed that SMK students encountered more difficulties in attending online learning classes compared with SMA students.